E-COMMERCE SUPPLY CHAIN MANAGEMENT IN COVID-19 - Kupalova, Halyna; 1goncharenkо, nataliia; Koreneva, Nataliia (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2021)
The article is devoted to the relevant problem of supply chain management in the e-commerce sector in the conditions of COVID-19. It is established that the sanitary and epidemiological restrictions (introduced as a result of the global COVID-19 pandemic) are changing the conditions for doing business in the field of e-commerce. Violations of supply chains, transport restrictions, increasing consumer demands for the quality of delivery of goods require a timely response of management, making informed decisions in the field of logistics. It is established that the existing logistics strategies in the conditions of COVID-19 are inefficient and need to be adjusted taking into account the influence of external factors. There is an urgent need to improve the methodological support for the analysis of the effectiveness of supply chains. For the analysis of supply chains in the field of e-commerce, it is advisable to use the SCOR-model, which includes three groups of logistics processes: supply planning, delivery, return. The decomposition of supply planning in the field of e-commerce is performed. The management block of planning provides forecasting of demand, studying of consumer priorities, planning of volume of stocks, definition of supply channels. The decomposition of supply planning in the field of e-commerce was performed. The organizational unit of delivery includes automation of processes of formation and registration of orders, the organization of delivery (a choice of transport, registration of the order for transport, control of timeliness of delivery), quality control of production and service of delivery. Under COVID-19, logistics outsourcing is an important area of ​​supply chain optimization in the field of e-commerce. To assess the effectiveness of outsourcing in supply chains in the field of e-commerce, it is proposed to use the indicator of integrated economic effect. The calculation of the above indicator will help to improve the information support of supply chain management, increase its efficiency.